Intertumor and intratumor heterogeneity of PIK3CA mutations in extramammary Paget's disease. Issue 5 (6th March 2022) - Kusaba, Yudo; Kajihara, Ikko; Myangat, Tselmeg Mijiddorj; Tanaka, Kenichiro; Sakamoto, Ryoko; Maeda‐Otsuka, Saki; Yamada‐Kanazawa, Saori; Sawamura, Soichiro; Kanemaru, Hisashi; Nishimura, Yuki; Nakamura‐Kashiwada, Kayo; Makino, Katsunari; et al.
Abstract: Although the prognosis of patients with extramammary Paget's disease (EMPD) treated with radical resection is good, the prognosis of EMPD with distant metastasis is very poor. PIK3CA mutations predict a good response to PIK3CA inhibitors. The aim of this study was to investigate the occurrence rate of PIK3CA mutations (including multiple mutations [MM]) related to the intertumor and intratumor heterogeneity in EMPD and to evaluate the correlation between these mutations and clinical parameters of EMPD. We performed droplet digital polymerase chain reaction to detect PIK3CA mutations (E542K, E545K, H1047R, and MM) in 68 patients with EMPD. In addition, we investigated the presence of PIK3CA mutations at multiple sites in 16 patients with PIK3CA mutations to assess the intratumor heterogeneity of PIK3CA mutations in EMPD. The frequency of one or more PIK3CA mutations in patients with EMPD was 30.8% (21/68). The frequency of E542K, E545K, H1047R, and MM were 10.2% (7/68), 13.2% (9/68), 11.7% (8/68), and 4.4% (3/68), respectively. No significant correlation was found between PIK3CA mutation patterns and clinical parameters. Of the 21 patients with PIK3CA mutations, 16 with tissue samples that could be analyzed at multiple sites were examined. The proportion of patients with the same PIK3CA mutations at all sites was 12.5% (2/16). The proportion of patients with the same PIK3CA mutations at least two or more sites, but not at all sites, was 31.2% (5/16). The proportion of patients with no PIK3CA mutations at other sites was 37.5% (6/16). The proportion of patients with other PIK3CA mutations at other sites was 18.7% (3/16). There is intertumor and intratumor heterogeneity of PIK3CA mutations. PIK3CA mutations in EMPD may be progressor mutations in EMPD.